2022
DOI: 10.7759/cureus.30984
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Allergic Fungal Rhinosinusitis: Does Age Make a Difference?

Abstract: BackgroundAllergic fungal rhinosinusitis (AFRS) is a hypersensitive response to fungi within the sinus cavity. Children represent a challenging group of patients with sinonasal disorders, as their sinus anatomy is not fully developed. This study aimed to determine the various clinical manifestations and management outcomes in children with AFRS. MethodsA retrospective chart review of children who underwent sinus surgery for AFRS at a tertiary healthcare center between 2005 and 2021 was performed. Demographics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…AFRS most commonly presents with nasal obstruction, nasal discharge and rhinorrhea, anosmia, and headaches. In the pediatric population, a much larger proportion of patients tend to present with facial skeletal abnormalities, osseous involvement, and ocular manifestations, such as proptosis [ 2 ]. One study found that 25% of pediatric patients diagnosed with AFRS presented with proptosis, while another found that closer to 50% of pediatric patients diagnosed with AFRS presented with such symptoms when compared to adult patients with the same diagnosis [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AFRS most commonly presents with nasal obstruction, nasal discharge and rhinorrhea, anosmia, and headaches. In the pediatric population, a much larger proportion of patients tend to present with facial skeletal abnormalities, osseous involvement, and ocular manifestations, such as proptosis [ 2 ]. One study found that 25% of pediatric patients diagnosed with AFRS presented with proptosis, while another found that closer to 50% of pediatric patients diagnosed with AFRS presented with such symptoms when compared to adult patients with the same diagnosis [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found pediatric disease relapse rates of around 55% at the one-year follow-up in patients who received endoscopic sinus surgery followed by nasal irrigation, endoscopic cleanings, and systemic steroid therapy [ 3 ]. Without postoperative adjuvant therapy, recurrence rates can be as high as 100% [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to EPOS 2020 [1], postoperative systemic corticosteroids improve short-term outcomes in AFRS and are likely to reduce long-term recurrence. Nasal and oral steroid therapy, oral and topical antifungal drugs (itraconazole, fluconazole), rinsing the nose with saline solution, immunotherapy, antihistamines, and antibiotic therapy are also used in the treatment process [25][26][27]. While using intranasal steroid, nebulized intranasal steroid is better than simple nasal steroid sprays.…”
Section: Discussionmentioning
confidence: 99%